Legal Regulation Problems for Online Gamblers - Firdha Sifana; Beniharmoni Harefa (KRTHA BHAYANGKARA, 2025)
The rapid development of digital technology has led to a new form of criminal activity online gambling which continues to expand within Indonesian society. However, the existing legal provisions, both in the old Criminal Code (KUHP) and the new National KUHP, do not explicitly regulate criminal sanctions for online gambling players. Meanwhile, the Electronic Information and Transactions Law (UU ITE) only addresses penalties for organizers and service providers. This has resulted in a legal vacuum, leading to uncertainty and weak law enforcement effectiveness. This study aims to examine the legal implications of the absence of specific regulations on criminal sanctions for online gambling players and to analyze the urgency of establishing a special regulation governing such sanctions in Indonesia. The research employs a juridical-normative method using statutory, conceptual, and case approaches to analyze the normative limitations and the need for criminal law reform. The findings indicate that Gustav Radbruch’s theory of legal certainty is relevant in explaining the necessity for more adaptive and clear legal provisions. The study recommends the formulation of a specific legal provision that defines online gambling players, outlines the elements of the offense, and differentiates levels of culpability, so that law enforcement and sentencing can be applied proportionally to the degree of involvement and fault of each offender.